CONSTITUTIONALIZING ROLE OF TERMS OF SERVICE OF SOCIAL MEDIA PLATFORMS AND PROPOSED SOCIAL MEDIA USER BILLS OF RIGHTS - Nino Shengelia (International Journal of Innovative Technologies in Social Science, 2020)
Multiple challenges and risks to democratic values and fundamental human rights emerge from the constitutulization processes of social media platforms. This article submits that more consideration has to be put on how private governance of social media platforms should be transparent, consensual, relatively stable in its application and how it should be enforced fairly. The values presented by the rule of law as well as traditional democratic principles of a sovereign state should inform the debate around contested relationship between the users and social media platforms. Digital constitutionalism is a concept that explains waves of constitutional counteractions as a result of a fast pace development of digital technologies. Digital constitutionalism is regarded as the idea that considers the constitutionalism of the digital society. This article focuses on examining constitutional tone of existing terms of service of a world leading social media platform Facebook and reviews potential value that digital Bills of Rights, intiated by various non-governmental organizations and individuals, may hold in shaping human rights’ compliant governance framework for social media platforms in the years to come. From the terms of service and bills of rights, it is based to show that Facebook is ready to show a peculiar configuration. At present, social media bills of rights and terms of service play the constitutionalizing roles. Nevertheless, it is not the aim of the current author to exhaust the topic, but rather to provide potential answers to the matters examined.